Pemberian Jasa Hukum Secara Cuma-Cuma Oleh Notaris Berdasarkan Undang-Undang Nomor 2 Tahun 2014 - Hasan Firdaus (Darma Cendika Catholic University, 2019)
One of the obligations of the notary is to provide legal services in terms of making deeds for free or without charging fees to the public who are not able to expressly regulate both the notary office law and the Notary Code of Ethics. This confirms that the notary is obliged to prioritize the service of the interests of the people and the State in carrying out their authority also required in accordance with the mandate of notary office law and the code of ethics, for example for poor people, notaries freeing honorarium in making deeds or other legal services regarding deeds, as mandated by Article 37 notary office law. The formulation of the problem in this normative juridical study is 1) Can the refusal to provide free legal services by a notary be justified? 2) What is the legal protection for people who cannot afford to get free legal services by a notary? The results obtained from this study are that: 1) Notary is not justified in rejecting the request of a client who is unable to request Notary legal services in the field of notary free of charge without collecting an honorarium, because of the provision of legal services in the field of notary free to people the incapable is a Notary's obligation that must be carried out as stipulated in Article 37 paragraph (1) of the notary office law. Rejection of clients who request legal services is a violation of Notary as stipulated in Article 37 paragraph (2) of notary office law. 2) Forms of legal protection from inadequate people who do not receive legal services from a notary for free are: a. The notary concerned is subject to administrative sanctions concerned. Administrative sanctions can be in the form of a temporary termination, or a respectful dismissal, or an award with disrespect according to the level and severity of the violation. The imposition of administrative sanctions on this Notary with the aim of having a deterrent effect both to the Notary concerned and to other Notaries. b. The incapable person can request legal services for notary matters to other Notaries.